VITALISM AS A CONCEPTUAL FOUNDATION OF EASTERN AND WESTERN PRACTICES OF COMPLEMENTARY AND ALTERNATIVE MEDICINE - Іщук, Наталія (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
The development of evidence-based medicine raises the question of how to assess medical practices that do not rely on strictly verified quantitative evidence, yet continue to be used. This issue is particularly relevant in relation to complementary and alternative medicine (CAM). Recent studies emphasize the heterogeneity of CAM, cooperation between conventional and complementary approaches, and growing interest in holistic models of health. In this context, the philosophical analysis of vitalism becomes important for clarifying the worldview foundations of CAM practices. The aim of the article is to provide a philosophical interpretation of the vitalistic foundations of CAM practices. The tasks are to outline the main philosophical discussions on the nature of vitalism, to analyze its philosophical and religious origins, and to systematize and compare the specific forms of its manifestation in Eastern and Western CAM practices. Research methods. The study is based on cultural-historical, comparative, and integrative approaches. The cultural-historical method makes it possible to trace the evolution of vitalistic concepts in religious, philosophical, and medical traditions. The comparative approach is used to identify differences between Eastern and Western forms of CAM. The integrative approach helps reveal the interaction between vitalism, holism, and contemporary interpretations of health and healing. Research results. The study demonstrates that vitalism remains an important conceptual basis of many CAM practices, although it should not be identified with holism as such. Vitalism is interpreted as a worldview grounded in the idea of a life force irreducible to purely physical and chemical processes, whereas holism functions as a broader methodological principle. Eastern CAM practices and related techniques preserve a strong connection with religious and philosophical traditions in which energy is understood as an impersonal immanent force that can be accumulated, balanced, and transformed. Western CAM practices, by contrast, are less rooted in Christian ontology and more often express vitalistic ideas in secularized, adaptive, or quasi-scientific forms. Discussion. The obtained results correspond with approaches that view CAM as a heterogeneous field of medical practices combining different worldview and therapeutic models. The analysis also demonstrates that some CAM practices are associated with vitalistic and holistic conceptions of the human being and health. At the same time, the distinction made between vitalism and holism clarifies the common tendency in the literature to conflate these concepts, showing that not all holistic approaches within CAM are strictly vitalistic. Conclusions. The article concludes that vitalism serves as one of the major conceptual foundations of complementary and alternative medicine; however, its forms differ significantly in Eastern and Western traditions. This difference reflects distinct religious and philosophical understandings of energy, health, and healing and clarifies the place of CAM within contemporary interdisciplinary discussions.